Aberrant enteric neuromuscular system and dysbiosis in amyotrophic lateral sclerosis. (1st January 2021) - Zhang, Yongguo; Ogbu, Destiny; Garrett, Shari; Xia, Yinglin; Sun, Jun
ABSTRACT: Amyotrophic Lateral Sclerosis is a neuromuscular disease characterized by the progressive death of motor neurons and muscle atrophy. The gastrointestinal symptoms in ALS patients were largely ignored or underestimated. The relationship between the enteric neuromuscular system and microbiome in ALS progression is unknown. We performed longitudinal studies on the enteric neuron system (ENS) and microbiome in the ALS human-SOD1 G93A (Superoxide Dismutase 1) transgenic mice. We treated age-matched wild-type and ALS mice with butyrate or antibiotics to investigate the microbiome and neuromuscular functions. We examined intestinal mobility, microbiome, an ENS marker GFAP (Glial Fibrillary Acidic Protein), a smooth muscle marker (SMMHC, Smooth Muscle Myosin Heavy Chain), and human colonoids. The distribution of human-G93A-SOD1 protein was tested as an indicator of ALS progression. At 2-month-old before ALS onset, SOD1 G93A mice had significantly lower intestinal mobility, decreased grip strength, and reduced time in the rotarod. We observed increased GFAP and decreased SMMHC expression. These changes correlated with consistent increased aggregation of mutated SOD1 G93A in the colon, small intestine, and spinal cord. Butyrate or antibiotics treated SOD1 G93A mice had a significantly longer latency to fall in the rotarod test, reduced SOD1 G93A aggregation, and enhanced enteric neuromuscular function. Feces from 2-month-old SOD1 G93A mice significantly enhanced SOD1 G93A aggregation in human colonoids transfected with a SOD1 G93A -GFP plasmid. Longitudinal studies of microbiome data further showed the altered bacterial community related to autoimmunity (e.g., Clostridium sp. ASF502, Lachnospiraceae bacterium A4), inflammation (e.g., Enterohabdus Muris, ), and metabolism (e.g., Desulfovibrio fairfieldensis ) at 1- and 2-month-old SOD1 G93A mice, suggesting the early microbial contribution to the pathological changes. We have demonstrated a novel link between the microbiome, hSOD1 G93A aggregation, and intestinal mobility. Dysbiosis occurred at the early stage of the ALS mice before observed mutated-SOD1 aggregation and dysfunction of ENS. Manipulating the microbiome improves the muscle performance of SOD1 G93A mice. We provide insights into the fundamentals of intestinal neuromuscular function and microbiome in ALS.